Exploring Malaysian street art: a comprehensive analysis of commissioned works through iconographical interpretation - Muhammad, Syafril Amir (2024)
The variety of visual art forms that exist in open spaces, particularly in urban areas, are now referred to as "street art," using a new phrase and special designation. It is a type of artwork that can be seen on the walls of streets and public areas. The two main categories are vandalism and commission. This research focuses solely on commission artwork because it is more prevalent and well-received in each state. In terms of historical development, the ‘street art' genre first emerged in Malaysia after UNESCO designated two historical cities, George Town and Malacca City, as World Heritage Sites in 2010. As a result of this recognition, the ‘street art' genre began to embellish both cities in order to promote and enhance the urban environment. As a result, this art form began to be used in other major Malaysian cities. This work's positive reception has developed in a variety of forms and interpretations. This study is based on 'street art' data collected from every state in Peninsular Malaysia. The artworks analyzed ranged from 2010 to 2021 and only focused on 2-dimensional works. The purpose of this study is to understand the formalistic elements and theme of 'street art' in Malaysia. This is due to the conclusion drawn from reading the literature, which was that the study's emphasis on aesthetic visuals in Malaysia's various states was not entirely enough. The theories of iconography and psychogeography are utilized to analyze the data of the "street art" work captured through photographs taken at each place in order to meet the study's objectives. The main focus for formalists is the size, format, subject, technique, color scheme, and perspective of space. While the theme consists of local activities, icons, events, and panoramas, The results of this study will reveal the identity of the 'street art' genre presented in the Malaysian context. It can also help the arts industry, especially street art performers, City councils, and NGOs, produce new forms of work in the future.